Suikoden III successor of fate = Genso suikoden - Shimizu, Aki (Tokyopop, 2004)
"As a young girl, Chris Lightfellow lost her father to the flames of war. Following in his footsteps, Chris entered military school and trained to become a knight. But when Chris' commanding officer is killed in battle, will Chris come into her own as a knight ... or follow her father's path to the grave?"--Cover, P. [4].